Visual Studio 2013 and .NET 4.5 expert cookbook : over 30 recipes to successfully mix the powerful capabilities of Visual Studio 2013 with .NET 4.5 /: over 30 recipes to successfully mix the powerful capabilities of Visual Studio 2013 with .NET 4.5. (2014) - Sur, Abhishek
No abstract available